2012
DOI: 10.1103/physrevlett.109.107201
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Orbit-Mediated Manipulation of Heavy-Hole Spin Qubits in Gated Semiconductor Nanodevices

Abstract: A novel spintronic nanodevice is proposed that is capable to manipulate the single heavy hole spin state in a coherent manner. It can act as a single quantum logic gate. The heavy hole spin transformations are realized by transporting the hole around closed loops defined by metal gates deposited on top of the nanodevice. The device exploits Dresselhaus spin orbit interaction which translates the spatial motion of the hole into a rotation of the spin. The proposed quantum gate operates on sub nanosecond time sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 52 publications
0
55
0
Order By: Relevance
“…To date, however, only partial anisotropy was demonstrated, e.g., in InAs SADs [20] and silicon nanowires [21]. Holes in GaAs are also subject to strong Dreselhaus and Rashba spin-orbit interactions, which introduce the coherent spin-flip tunneling [12,13]. In silicon DQDs these interactions are absent, leading to Pauli spin blockade [21][22][23].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, however, only partial anisotropy was demonstrated, e.g., in InAs SADs [20] and silicon nanowires [21]. Holes in GaAs are also subject to strong Dreselhaus and Rashba spin-orbit interactions, which introduce the coherent spin-flip tunneling [12,13]. In silicon DQDs these interactions are absent, leading to Pauli spin blockade [21][22][23].…”
mentioning
confidence: 99%
“…Our hole device is different from the electronic system in two aspects. First, the HH in III-V materials experiences a strong spin-orbit interaction, causing the hole spin to rotate during tunneling [12,13,26]. In electronic devices this process was found to be orders of magnitude weaker [28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bh, 78.20.Ls, 78.40.Fy, 42.50.Tx Light with orbital angular momentum (OAM), referred to as twisted light, is a relatively new field of research which has become increasingly popular [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] since Allen et al showed how twisted light beams can be easily generated from conventional laser beams [18]. Recently, the theoretical foundation of the optical excitation of solids and nanostructures with twisted light has been established [19][20][21][22][23][24][25][26][27], and experimental studies with twisted light on semiconductors have been carried out [28,29].One motivation for such studies is the prospect of using the large amounts of angular momentum that twisted light can carry in order to control the spin dynamics of electrons, thus adding a flexible tool to the active field of spin control [30][31][32][33][34][35][36][37][38][39]. In this context two different mechanisms need to be distinguished.…”
mentioning
confidence: 99%
“…45,46 In addition to optical coherent control of hole spins in self-assembled quantum dots, 39,41,47,48 there are several suggestions for electrical manipulation of hole spins. [49][50][51] Such electrical control has recently been demonstrated for hole spins in III-V nanowire quantum dots, 52 and coherence times have now been measured for hole spins in Ge-Si core-shell nanowire quantum dots. 53 The very recent achievement of the few-hole regime in lateral gated double-dot devices, 54 suggests that previous highly successful measurements performed for electron spins [55][56][57][58][59][60] can now be performed for hole spins, which show promise for much longer coherence times.…”
Section: Introductionmentioning
confidence: 99%